A New Species of Pleurostachys (Cyperaceae) from Atlantic coastal Brazil - Thomas, W. Wayt; Alves, Marccus V.; Trevisan, Rafael (Phytotaxa, 2013)
Pleurostachys arcuata is described as a new species endemic to the Atlantic forest of Brazil.  It is illustrated and is compared to other species of Pleurostachys.  It has the large achenes of P. macrantha but has small, axillary synflorescences similar to those of P. gaudichaudii.